Association between miR-499 rs3746444 and the susceptibility of hepatocellular carcinoma - Yu, H; Wang, Y; Wang, S; Sun, N (Cellular and Molecular Biology, 2016)
Considering the inconsistent association between miR-499 rs3746444 and the risk of hepatocellular carcinoma (HCC), it is critical to carry out a meta-analysis in order to produce a precise result. Therefore, a meta-analysis was performed. All of the potential eligible studies were screened based on the following databases, including PubMed, EMBASE, Medline and China National Knowledge Internet (CNKI) up to December 2015. The associations between miR-499 rs3746444and HCC susceptibility was quantified using odds ratios (ORs) with its 95% confidence intervals (CIs). Nine case-control articles were included in the analysis. A total of 2593 cases and 3259 controls were included. The pooled OR was 1.27 (95% CI: 1.10 - 1.48, P = 0.002) which suggested thatmiR-499 rs3746444 was significantly associated with an increased the risk of HCC. Subgroup analysis was performed by ethnicity, miR-499 rs3746444 was significantly associated with an increased the risk of HCC in Asians (OR = 1.31, 95% CI = 1.10-1.55; P = 0.002). However, no significant result was found in Caucasians (OR = 1.10, 95% CI = 0.84-1.44; P = 0.49). In addition, miR-499 rs3746444 was significantly associated with an increased the risk of HCC in subjects with HBV infection OR = 1.31, 95% CI = 1.09-1.58; P = 0.004). This study suggested that miR-499 rs3746444 might play an important role in the development of HCC.